An in-library ligation strategy and its application in CRISPR/Cas9 screening of high-order gRNA combinations. Issue 11 (7th June 2022) - Lu, Zhike; Ni, Ke; Wang, Yingying; Zhou, Yangfan; Li, Yini; Yan, Jianfeng; Song, Qingkai; Liu, Min; Xu, Yujun; Yu, Zhenxing; Guo, Tiannan; Ma, Lijia
Abstract: Simultaneous targeting multiple genes is a big advantage of CRISPR (clustered regularly interspaced short palindromic repeats) genome editing but challenging to achieve in CRISPR screening. The crosstalk among genes or gene products is a common and fundamental mechanism to ensure cellular stability and functional diversity. However, the screening approach to map high-order gene combinations to the interesting phenotype is still lacking. Here, we developed a universal in-library ligation strategy and applied it to generate multiplexed CRISPR library, which could perturb four pre-designed targets in a cell. We conducted in vivo CRISPR screening for potential guide RNA (gRNA) combinations inducing anti-tumor immune responses. Simultaneously disturbing a combination of three checkpoints in CD8+ T cells was demonstrated to be more effective than disturbing Pdcd1 only for T cell activation in the tumor environment. This study developed a novel in-library ligation strategy to facilitate the multiplexed CRISPR screening, which could extend our ability to explore the combinatorial outcomes from coordinated gene behaviors.